Reflections on the Asan Medical Center Plastic Surgery Visit: A Well-Organized Specialized Team and Excellent Leadership - Hatan Mortada (Archives of Plastic Surgery)
Asan Medical Center in Seoul, South Korea, is renowned for its excellence in plastic and reconstructive surgery. This paper aims to share insights from a 2-week fellowship experience in the Department of Plastic Surgery, led by Professor Jong Woo Choi. The program offers comprehensive clinical observership, including participation in daily conferences, ward rounds, outpatient clinics, and surgical procedures. Observers gain exposure to complex microsurgical cases, benefiting from the department's high case volume and state-of-the-art facilities. The center's commitment to pioneering research and innovation provides exposure to cutting-edge techniques and fosters collaboration. Personal reflections highlight the program's impact on professional development and the supportive learning environment created by Professor Hong and his team. This fellowship offers an unparalleled opportunity for surgeons to enhance their expertise in reconstructive microsurgery, engage with leading experts, and witness advanced patient care. The experience provides valuable insights and inspiration for those considering similar educational pursuits in plastic and reconstructive surgery.